Functional identification of the sex pheromone receptor MsepOR6 in the natural population of Mythimna separata (Walker) - ZHANG Yongle; CHENG Jianjun; ZHENG Jingjun; DU Yongjun (浙江大学学报. 农业与生命科学版)
In order to further understand the calling behavior of Mythimna separata (Walker) (Lepidoptera, Noctuidae) and explore the olfactory molecular recognition mechanism of male moths to intra- and inter-specific sex pheromones, the male moths collected by sex pheromone trapping with the mixture of Z11-16：Ac and Z11-16：OH in the field were used in this study. According to the reported fragment, we amplified the full-length sequence of MsepOR6 by rapid amplification of cDNA ends (RACE) technology. The responses of MsepOR6 cRNA to pheromone compounds were identified by two-electrode voltage clamp. The behavioral responses of male moths to active compounds were further verified by sex pheromone trapping experiment in the field. Electrophysiological assay results showed that MsepOR6 is one of the sex pheromone receptor genes, which was sensitive to two intra-specific sex pheromones of Z11-16：Ald and 16：Ald, and four inter-specific sex pheromones of Z9-14：Ac, Z7-12：Ac, Z9-16：Ac, and Z9-14：OH. Field bioassay results showed that Z9-14：Ac was antagonist and Z7-12：Ac was synergist in sex pheromone trapping of male moths. This study identified the function of MsepOR6 in the natural population of male moths, which is helpful to understand the regulatory mechanism of calling behavior and provides theoretical support for further development of sex pheromone application technology.